2022
DOI: 10.1002/chem.202104074
|View full text |Cite
|
Sign up to set email alerts
|

Ylide‐Stabilized Phosphenium Cations: Impact of the Substitution Pattern on the Coordination Chemistry

Abstract: On the occasion of the 60th birthday of Prof. Holger Braunschweig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 116 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…1B) 24 which have particularly been applied for the synthesis of main group complexes leading to seminal contributions in structure, bonding, and reactivity. [25][26][27][28][29] Analogous complexes with transition metals are rare, [30][31][32][33] but have demonstrated the unusual donor strength of the respective phosphonio-carbene/yldiide ligands. [34][35][36] Likewise phosphonio-carbene complexes of the actinides have been reported, but only with the parent phosphoranomethylide ligand (C and D), [37][38][39][40] which was synthesized in the coordination sphere of the metal and was shown to produce short actinide-carbon bonds with some degree of multiple bonding character.…”
mentioning
confidence: 99%
“…1B) 24 which have particularly been applied for the synthesis of main group complexes leading to seminal contributions in structure, bonding, and reactivity. [25][26][27][28][29] Analogous complexes with transition metals are rare, [30][31][32][33] but have demonstrated the unusual donor strength of the respective phosphonio-carbene/yldiide ligands. [34][35][36] Likewise phosphonio-carbene complexes of the actinides have been reported, but only with the parent phosphoranomethylide ligand (C and D), [37][38][39][40] which was synthesized in the coordination sphere of the metal and was shown to produce short actinide-carbon bonds with some degree of multiple bonding character.…”
mentioning
confidence: 99%
“…27 Due to the architecture of the YPhos ligands, the phosphonium moiety is usually facing toward the metal center, which allows for further attractive interactions. Crystallographic studies on gold complexes with PPh 3 -substituted YPhos ligands revealed a short gold-arene distance (Figure 6), 28 which was further confirmed by quantum theory of atoms-in-molecules (QTAIM) studies as being an attractive interaction between the metal and the ipso and ortho carbon atoms of one of the PPh 3 phenyl rings. 29 Comparative studies on LAuCl with YPhos ligands with different aryl groups in the backbone showed the highest BCP electronic density for the ortho-tolyl and mesityl substituted ligands, suggesting that the LAu + species with these ligands experiences the highest stabilization and in turn exhibit the best catalytic performance.…”
Section: The Importance Of Secondary Metal Ligand Interactionsmentioning
confidence: 95%
“…Unlike those, pnictogenium ions are also strong electrophiles, which can be attributed to the positive charge that attracts any nucleophile present. Consequently, the vast majority of phosphenium ions, [R 2 P] + , [2–33] arsenium ions, [R 2 As] + , [34–51] stibenium ions, [R 2 Sb] +[52–59] and bismuthenium ions, [R 2 Bi] + , [60–72] reported in the literature are either affected by ion pairing or stabilized by electron‐rich ligands or substituents, which inter‐ or intramolecularly fill the vacant p‐orbital. These electronically stabilized pnictogenium ions often have a dramatically reduced Lewis acidity and cannot be regarded as genuine 6 VE species as they fulfill or even exceed the octet rule.…”
Section: Introductionmentioning
confidence: 99%